Refinement of the English language teaching textbook evaluation checklist - Nimehchisalem, Vahid; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2015)
The English Language Teaching (ELT) Textbook Evaluation Checklist was developed in response to the need for a reliable, valid and practical instrument to evaluate English language teaching textbooks. The checklist was qualitatively developed by a review of the literature (Mukundan & Ahour, 2010; Mukundan et al., 2011a) and was refined through qualitative (Mukundan et al., 2011b) and quantitative (Mukundan & Nimehchisalem, 2012a) methods. As the validation test results of the checklist (Mukundan & Nimehchisalem, 2012b; Nimehchisalem & Mukundan, 2013) indicated, it could be refined further to improve its validity, reliability and practicality. The present study discusses the modifications made to the checklist following the comments of a panel of experts (n=3), who were sent a copy of the old version of the checklist. They commented on the comprehensiveness, importance and clarity of the domains and items of the checklist independently. The qualitative method was used to collect and analyse the data. The checklist was refined based on the experts' comments; problematic items were removed or revised and a scoring guide was added to it. The refined instrument is more economical than its previous version, and yet further research is required to test its validity empirically.